PENGARUH VARIASI PENGGUNAAN LAHAN PADA BERBAGAI FORMASI GEOLOGI TERHADAP RESESI ALIRAN DASAR DI DAS WURYANTORO PROPINSI JAWA TENGAH - Bokiraiya Latuamury; sudarmadji sudarmadji; slamet suprayogi (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2017)
In the environmental viewpoint, water and land characteristics are strongly influenced by some aspects such as layout, position, landscape development, natural factors and human activity impact.Spatial aspects of land and water resources are the asset of spatial-based national development. Land resources management need to consider the characteristic of both renewable and nonrenewable land resources.Hydrological characteristics is a result of interaction and interrelation of human socio-economic parameters with some watershed physical factors. Apart from that, besides land use as physical factors, there are some other factors such as morphometry, lithology, geomorphology and geology. They are all naturally come from a watershed that cannot be altered by a human (unmanageable). Some combination of watershed physical factors and the manageable factors such as land use plan, slope, and slope length will give a specific watershed response to the rainfall. Eventually, this affects the large-small of river flows behavior. Baseflow river is an essential substance for the development of water resource management strategies at watershed scale. Therefore, this study aimed to estimate baseflow river recession at various geological formation. It also influences characteristics of baseflow recession in Wuryantorosub-watershed at Wonogiri district. Simultaneous Statistical Analysis (ANOVA) and partial (t-test) analysis show that there is a significant influence on the variation of land use in diverse geological formations toward the baseflow recession, with a determination coefficient value - Adjusted R-square is 58.1%.The simultaneous analysis describes a simultaneously effect of recession baseflow coefficient with value test of the test F table > F count at a level of confidence by 5%, and a partial analysis shows that all land use variations in three geological formations significantly influence baseflow recession. Recession model of these two relations is Y = 1.426 + 0,583X1 + 0,384X2 + 0,269X3. This condition indicates that baseflow recession is influenced by some basic by a number of entire environmental attributes. Thus, there will be a sustainable synergy of baseflow recession management that maintain river pattern by the surrounding inhabitant as an alternative water supply for local communities. Keywords: Baseflow, perennial river, variations in land use, geological formations